Preclinical Pharmacokinetics, Tissue Distribution, and Plasma Protein Binding of Sodium (±)-5-Bromo-2-(α-Hydroxypentyl) Benzoate (BZP), an Innovative Potent Anti-ischemic Stroke Agent - Tian, Xin; Li, Hong-Meng; Wei, Jing-Yao; Liu, Bing-Jie; Zhang, Yu-Hai; Wang, Gao-Ju; Chang, Jun-Biao; Qiao, Hai-Ling (Frontiers in Pharmacology, 2016)
Sodium (±)-5-bromo-2-(α-hydroxypentyl) benzoate (BZP) is a potential cardiovascular drug and exerts potent neuroprotective effect against transient and long-term ischemic stroke in rats. BZP could convert into 3-butyl-6-bromo-1(3H)-isobenzofuranone (Br-NBP) in vitro and in vivo. However, the pharmacokinetic profiles of BZP and Br-NBP still have not been evaluated. For the purpose of investigating the pharmacokinetic profiles, tissue distribution and plasma protein binding of BZP and Br-NBP, a rapid, sensitive and specific method based on liquid chromatography coupled to mass spectrometry (LC-MS/MS) has been developed for determination of BZP and Br-NBP in biological samples. The results indicated that BZP and Br-NBP showed a short elimination half-life, and pharmacokinetic profile in rats (3, 6 and 12 mg/kg; i.v.) and beagle dogs (1, 2 and 4 mg/kg; i.v.gtt) were obtained after single dosing of BZP. After multiple dosing of BZP, there was no significant accumulation of BZP and Br-NBP in the plasma of rats and beagle dogs. Following i.v. single dose (6 mg/kg) to rats, BZP and Br-NBP were distributed rapidly into all tissues examined, with the highest concentrations of BZP and Br-NBP in lung and kidney, respectively. The brain distribution of Br-NBP in middle cerebral artery occlusion (MCAO) rats was more than in normal rats (P<0.05). The plasma protein binding degree of BZP at three concentrations (8000, 20000 and 80000 ng/mL) from rat, beagle dog and human plasma were 98.1 98.7%, 88.9 92.7% and 74.8% 83.7% respectively. In conclusion, both BZP and Br-NBP showed short half-life, good dose-linear pharmacokinetic profile, wide tissue distribution and different degree protein binding to various species plasma. This was the first preclinical pharmacokinetic investigation of BZP and Br-NBP in both rats and beagle dogs, which provided vital guidance for further preclinical research and the subsequent clinical trials.